2020
DOI: 10.1007/s00520-019-05272-4
|View full text |Cite
|
Sign up to set email alerts
|

Vulvovaginal atrophy (VVA) in breast cancer survivors (BCS) is still an unmet medical need: results of an Italian Delphi Panel

Abstract: Purpose VVA is a common disease, with approximately 50% of all postmenopausal women having related symptoms. VVA has a significant impact on the personal and sexual lives and on many aspects of women's self-esteem and emotional well-being. It is particularly frequent and severe in patients treated for BC, where it originates significant economic and social costs. Given the lack of published evidence on this subject, a Delphi Panel was carried out to evaluate: & The epidemiology of VVA and of its risk-factors/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Considering the higher anxiety levels of AI patients, they should be actively informed that sexual dysfunction, that has also a relevant social cost [31], will improve after AI stopping and could be safely and effectively treated with nonhormonal treatments, like ospemifene [32]. While waiting, it is important to suggest trying to empower them telling that they can do something important even during AI use to keep up sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the higher anxiety levels of AI patients, they should be actively informed that sexual dysfunction, that has also a relevant social cost [31], will improve after AI stopping and could be safely and effectively treated with nonhormonal treatments, like ospemifene [32]. While waiting, it is important to suggest trying to empower them telling that they can do something important even during AI use to keep up sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen deficiency induces similar atrophic changes also in the urinary tract, where estrogen receptors are abundantly expressed [ 16 , 22 ]. Consequently, women with GSM often suffer from urinary symptoms such as recurrent infections, incontinence, urgency, and dysuria [ 5 , 17 , 23 ]. Other anatomical and physiological changes in urogenital tissues include that the vagina may shrink, shorten, and lose its elasticity and flexibility.…”
Section: Etiology Of Gsmmentioning
confidence: 99%
“…Although genitourinary symptoms are usually caused by naturally occurring postmenopausal estrogen loss, they also can be caused by chemotherapy and/or endocrine therapy for breast cancer (Mac Bride, Rhodes, & Shuster, 2010; The North American Menopause Society, 2020). Breast cancer survivors suffer from genitourinary symptoms, yet they are under-reported (Baumgart et al, 2011), under-assessed, and under-treated (Biglia, Pup, Masetti, Villa, & Nappi, 2020;Cook, Sutherland, Baum, Schover, & Newman, 2018;Lester & Bernhard, 2009;Moral et al, 2018).…”
Section: Relationship With Sexual Functioningmentioning
confidence: 99%
“…In addition, the prevalence of genitourinary symptoms varies due to differences in symptom assessments. In prior studies of breast cancer survivors, 32% to 75% reported at least one genitourinary symptom such as vaginal discharge, irritation, bleeding, dryness, and urine control problems (Baumgart et al, 2011;Biglia et al, 2020;Chin et al, 2009;Lester, Bernhard, & Ryan-Wenger, 2012). Many of these studies with selected samples suggested the need for a large sample estimate in a group of women unselected for symptoms of any kind.…”
Section: Relationship With Sexual Functioningmentioning
confidence: 99%